Association of Exclusive Breastfeeding, Dietary Diversity, and Feeding Practices with Stunting among Under-Five Children - Nursahida hida; Darmin Darmin; Alkhair Alkhair (MESINA (Medical Scientific Journal), 2026)
Stunting is a chronic nutritional problem that can hinder children’s growth and development. This study was conducted to determine the relationship between exclusive breastfeeding, dietary diversity, and parenting practices and the prevalence of stunting among toddlers in the service area of the Penana’e Community Health Center. This study used a quantitative analytical design with a cross-sectional approach. The sample size for this study was 78 toddlers selected using simple random sampling. Data were collected via questionnaires and anthropometric measurements, then analyzed using the Chi-Square test and Fisher’s Exact Test. The results showed that 38 toddlers (48.7%) were classified as stunted, while 40 toddlers (51.3%) were not stunted. The majority of respondents had a history of insufficient exclusive breastfeeding (57.7%), insufficient dietary diversity (53.8%), and parenting practices classified as good (94.9%). The results of the analysis show that exclusive breastfeeding is not significantly associated with the incidence of stunting, with a p-value of 0.672. Similarly, dietary diversity does not show a significant association with the incidence of stunting, with a p-value of 0.807, and parenting practices are also not significantly associated with the incidence of stunting, with a p-value of 0.352. Thus, it can be concluded that exclusive breastfeeding, dietary diversity, and parenting practices do not have a statistically significant association with the incidence of stunting in toddlers.